Duration, convexity and time as components of bond returns. - Leo, Pui Ying. (2008)
The paper seeks to determine the components of bond returns when yield changes is not instantaneous. The traditional measure of bond returns, duration and convexity, is accurate only for an instantaneous yield change. The inclusion of bond theta in the bond return analysis significantly improves the returns analysis when yield change is not instantaneous.